Conceptual positions of category of safety in legal science (Journal of actual problems of jurisprudence, 2018)
The concept of security is considered in this article. In legal science, security is understood as a condition of protection of interests of the individual, society and the state from threats. Conclusion that the safety and stability are interconnected to each other and determine each other was drawn.The components of safety – rights and individual freedoms, interests of society, interests of the state are defined. The comparative analysis of legal practice of Russian Federation and Republic of Kazakhstan is carried out in area of providing of national safety. Conclusion about the necessity of further perfection of legislative base of Republic of Kazakhstan in the area of providing of national safety was made.Key words: safety, human rights, globalization, legal interests, threat, protection of human rights, civil society.